Parent Perception Of Students On Physical Education in SMP Negeri 32 Padang - Wulandari, Wulandari; Ernawati Chan; Perwira, Icshan (Jurnal Guru Peneliti Professional, 2019)
This research is motivated by the perceptions of parents of students towards learning Sports and Health Physical Education (PJOK) at SMP Negeri 32 Padang, Koto Tangah District in the 2017/2018 school year. This is because the perceptions of parents of students in attaining PJOK learning only assess the success of the lesson from the high scores on the exam, and for PJOK it is considered not so important, so that parents pay less attention and support their children in participating in PJOK learning. This type of research is classified in descriptive research. The population in this study were all parents of students in SMP Negeri 32 Padang, totaling 604 people. The sampling technique used was purposive sampling. The sample is taken 10%, the number of samples is 60 people. The data collection technique used was a questionnaire and a list of questions using a Likert scale. The research data analysis technique used descriptive analysis with a percentage. The results of the study concluded that in general the perceptions of parents of students towards learning PJOK at SMP Negeri 32 Padang were in the enough category with a percentage of 50.00%. Based on this, the researcher suggests parents of students to pay more attention to and support their children in learning PJOK. With the support of parents for learning PJOK will have a better impact on learning outcomes of PJOK.